2015
DOI: 10.3765/salt.v0i0.2593
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Pragmatics, or. Why We Shouldn't be Afraid of Embedded Implicature

Abstract: This paper examines a particular case of embedded pragmatic effect, here dubbed local pragmatic enrichment. I argue that local enrichment is fairly easily accommodated within semantic theories which take content to be structured. Two standard approaches to dynamic semantics, DRT and Heimian CCS, are discussed as candidates. Focusing on cases of local enrichment of disjuncts in clausal disjunctions, I point out that in these cases, local enrichment is driven by global felicity requirements, demonstrating that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…I had lunch with Frances on Wednesday. Simons (2007Simons ( , 2010Simons ( , 2011 has demonstrated that embedded verb clauses can be used as objects of pragmatic inference, and these clauses form the main part of speech content. Therefore, ( 6) is the natural response of any answer in (5), which requires that the hearer should recognize the content of the clause as the possible answer to the question.…”
Section: Simons' Insight: Local Pragmaticsmentioning
confidence: 99%
“…I had lunch with Frances on Wednesday. Simons (2007Simons ( , 2010Simons ( , 2011 has demonstrated that embedded verb clauses can be used as objects of pragmatic inference, and these clauses form the main part of speech content. Therefore, ( 6) is the natural response of any answer in (5), which requires that the hearer should recognize the content of the clause as the possible answer to the question.…”
Section: Simons' Insight: Local Pragmaticsmentioning
confidence: 99%